Vācaspatimiśra's Tattvasamīkṣā : the earliest commentary on Maṇḍanamiśra's Brahmasiddhi - Vācaspatimiśra, active 976-1000.; Acharya, Diwakar; Nepal Research Centre (Wiesbadan, GmbH : Franz Syeiner Verlag, 2006)
Critically edited text of classical commentary on Brahmasiddhi of Maṇḍanamiśra, treatise on Advaita ontology; includes exhaustive introduction; based on rare manuscript in National Archives, Kathmandu.
Originally presented as the author's thesis (Doctroral--University of Hamburg, 2004).
Includes bibliographical references (p. [361]-373) and indexes.
In Sanskrit; introd. and notes in English.
Keywords: Maṇḍanamiśra; Advaita -- Early works to 1800.; Vedanta -- Early works to 1800.